Solid Lipid Nanoparticles: Peculiar Strategy to Deliver Bio-Proactive Molecules - Minocha, Neha; Sharma, Nidhi; Verma, Ravinder; Kaushik, Deepak; Pandey, Parijat (Recent Patents on Nanotechnology, 2023)
Background: Novel Drug Delivery Systems (NDDS) provide numerous benefits compared to conventional dosage forms. Poor aqueous solubility, low bioavailability, frequent dosing, and particular hydrophilic lipophilic character of the drug are the biological factors associated with the traditional systems leading to the development of SLNs. Objective: For improving the solubility profile, enhancing the bioavailability, and attaining the best possible therapeutic effect of lipid inclined or aqueous inclined drug, formulating solid lipid nanoparticles is the best choice. Methods: Solid Lipid Nanoparticles (SLNs) have been projected as a colloidal carrier system with a size of 50–1,000 nm, collectively combining the benefits of other colloidal systems like liposomes, emulsions, etc., for delivering the drug at the target site. High absorption, high stability, and efficient drug packing enhance the pharmacokinetic and pharmacodynamic properties of the packed drug. Result: Solid Lipid Nanoparticles can be developed in different dosage forms and administered via routes such as nasal, rectal, oral, topical, vaginal, ocular, and parenteral. They have higher physicochemical stability and the batch size can be easily scaled up at a low cost. Lipophilic as well as hydrophilic drugs can be easily incorporated into solid lipid nanoparticles. Conclusion: In this manuscript, the authors have reviewed different aspects of solid lipid nanoparticles, major principles behind mechanism methods, recent patents, applications, and therapeutic potentials of solid lipid nanoparticles.
Keywords: nanocarriers